Scaffolding EARGD: On Effective Teaching Writing for EFL - Herwanis, Delfia; Sarinauli, Barep; Zakaria, Rahmanita; Yusdiana, Emy (International Journal for Educational and Vocational Studies, 2021)
This paper is concerned with the applying scaffolding in learning of writing for English Second Language learners. A quantitative approach used to address the research problem in this paper. The subject is the second semester English Department students of IAIN Takengon, it was purposively sampled for the study. The pre- and post-test responses were evaluated using the same rubric, modified to evaluate students writing content, to increase the reliability of the assessment. The same assessment given in the pre-test was used after the treatment. The assessment was used to determine whether students could demonstrate the application of new knowledge, language, and variation in organizational structure and whether scores had improved. The results have shown that the use of scaffolding EARGD is effective to increase students writing ability.